Power Plays Energy Options in the Age of Peak Oil - Rapier, Robert; SpringerLink (Online service) (Berkeley, CA : Apress, 2012)
Many people wonder: Are we really running out of oil, or is it all a ruse to drive prices up? Is nuclear power safe and economical? Is solar energy really the key to providing plenty of carbon-free energy? Do we have enough natural gas or coal to make any loss of oil production irrelevant? In Power Plays: Energy Options in the Age of Peak Oil, energy expert Robert Rapier helps readers sort through energy hype, doom and gloom, and misinformation to understand what really matters in energy, and how it impacts individuals, investors, businesspeople, and policy makers worldwide. The book covers the overall global energy situation, the particular risks for the U.S. with its present energy mix, the energy outlook for the developed world and emerging economies like China and India, what peak oil really means, and the present and likely future of natural gas, coal, oil, nuclear power, and alternative energy sources. The book also addresses common misconceptions. For instance, most readers are likely unaware that the U.S. is the third-largest oil producer in the world. Or that Canada leads the U.S. in per capita oil consumption. It will also highlight interesting facts$1 (Bfor example, China has solved part of its energy challenge by mandating solar hot water systems in all new construction. Most importantly, the book will provide specific energy insights unavailable elsewhere and help individuals and business planners chart future actions and decisions. With the disaster at Fukushima, the discovery of the Marcellus shale natural gas deposits, the increasing efficiency of solar electricity installations, and the unsustainable supply of oil, the energy outlook has changed greatly over the last couple of years. What$1 (Bs now required is just what this book delivers: a sober, even-handed account of our energy resources, present and future, that will help people plan for a world without cheap energy.s
Keywords: Economics; Economics/Management Science; Business/Management Science, general